Native Mass Spectrometry of Photosynthetic Pigment-Protein Complexes - Zhang, Hao (2013)
Native mass spectrometry, or as is sometimes called “native electrospray (ESI)” allows proteins in their native or near-native protein in solution to be introduced into gas phase and interrogated by MS. This approach is now a powerful tool to investigate protein complexes. This article reviews the background of native MS of protein complexes and describes its strengths, taking photosynthetic pigment-protein complexes as examples. Native MS can be utilized in combination with other MS-based approaches to obtain complementary information to that provided by tools such as X-ray crystallography and NMR spectroscopy to understand the structure-function relationships of protein complexes. When additional information beyond that provided by native MS is required, other MS-based strategies can be successfully applied to augment the results of native MS.